Performance comparison of secondary and tertiary treatment systems for treating antibiotic resistance. (15th December 2017) - Lamba, Manisha; Ahammad, Shaikh Ziauddin
Abstract: Rapid emergence of antibiotic resistance (AR) in developing countries is posing a greater health risk and increasing the global disease burden. AR proliferation mediated by treated/untreated discharges from sewage treatment plants (STPs) is a prime public health concern. Efficient sewage treatment is among our key defenses against the dissemination of infectious diseases. The present study aims to estimate the efficiency of aerobic [activated sludge process (ASP) and modified trickling filter (MTF)] and anaerobic reactors (anaerobic flow-through reactor) along with the three disinfection techniques (UV, ozone and chlorination) in reducing ARB and ARGs present in the domestic sewage. The three treatment systems were operated at different HRTs for 1 year and their performances in terms of treatment of conventional and emerging pollutants (ARB and ARGs) were assessed. The results indicated higher removal of ARB and ARGs in aerobic reactors compared to anaerobic reactor. Treatment studies in various bioreactors showed that the use of MTF along with UV/Ozone was superior to ASP and anaerobic flow-through reactor in reducing both the conventional and emerging pollutants. However, higher reduction of the pollutants was observed at higher HRTs. Though complete removal of coliforms and ARB was observed by treating the wastewater using MTF followed by UV or ozone but substantial levels of ARGs were observed in the effluent. Therefore, different advanced and effective treatment technologies such as filtration (RO), use of zero valent iron, TiO2 photocatalysis and other strong oxidizing agents which can ensure complete removal of ARGs along with ARB need to be evaluated. Though addition of these units will increase the treatment cost, but the increased cost would be negligible compared to the present disease burden of AR. Graphical abstract: Highlights: Aerobic treatment is superior to anaerobic treatment process. MTF is more effective than ASP and AnR in removing conventional and emerging pollutants. Complete removal of ARB but incomplete removal of ARGs is achieved using MTF followed by UV/Ozone. MTF followed by UV/Ozone is less efficient in reducing ARGs compared to ARB.